Palmatine antioxidant and anti-acetylcholinesterase activities: A pre-clinical assessment - Chaves, Soane Kaline Morais; Afzal, Muhammad Inam; Islam, Muhammad Torequl; Hameed, Aneela; da Mata, Ana Maria Oliveira Ferreira; da Silva Araújo, Lidiane; Ali, Shinawar Waseem; Rolim, Hercília Maria Lins; de Medeiros, Maria das Graças Freire; Costa, Emmanoel Vilaca; Salehi, Bahare; Martins, Natália; et al. (Cellular and Molecular Biology, 2020)
There is evidence that palmatine (PA), an alkaloid isolated from the Guatteria friesiana plant, has some important biological activities, including anti-inflammatory and antidepressant effects. In this study, the antioxidant and anti-acetylcholinesterase (AChE) effects of PA were assessed. The antioxidant capacity was evaluated in vitro and in vivo through 7 distinct assays, and the anti-AChE activity was determined in vitro. The standards, trolox and ascorbic acid were used for the in vitro antioxidant test, while hydrogen peroxide was selected as a stressor for the Saccharomyces cerevisiae test. Additionally, PA was also combined with trolox and ascorbic acid to determine the likelihood of synergistic effects occurrence to what concerns to antioxidant potential. PA exhibited a potent and concentration-dependent antioxidant potential, although a stronger antioxidant activity was stated using the PA + trolox combination. PA was also found to inhibit AChE activity when compared to the negative control. Thus, PA may be viewed as a promissory phytotherapeutic agent to manage oxidative stress-mediated neurological diseases, especially the Alzheimer’s and Parkinson’s diseases.